Characteristics of effective shots on goal in the games of the first league team of the championship of Ukraine "Helios" Kharkіv - Andrii Pertsukhov (Kharkiv State Academy of Physical Culture, 2018)
Purpose: to determine the quantitative indicators of effective shots on goal in the games of the team "Helios" Kharkiv. Material & Methods: analysis of scientific and methodological literature, registration of technical and tactical actions, methods of mathematical statistics. The research of the competitive activity of the first league team of the championship of Ukraine "Helios" Kharkiv in the season 2017-2018. Results: in the article the data characterizing the peculiarities of performance of effective shots on goal in the games of the team "Helios" Kharkiv. Conclusion: data of the conducted research testify to the differences in the quantitative indicators of the effective shots on goal made by the players of the teams of the first league of Ukraine in different intervals of playing time, from different zones of the football field.